Genotype-dependent effects of COMT inhibition on cognitive function in a highly-specific, novel mouse model of altered COMT activity - Barkus, C; Korn, C; Stumpenhorst, K; Laatikainen, L; Ballard, D; Lee, S; Sharp, T; Harrison, P; Bannerman, D; Weinberger, D; Chen, J; Tunbridge, E (Nature Publishing Group, 2016)
Catechol-O-methyltransferase (COMT) modulates dopamine levels in the prefrontal cortex (PFC). The human gene contains a polymorphism (Val158Met) that alters enzyme activity and influences PFC function. It has also been linked with cognition and anxiety, but findings are mixed. We therefore developed a novel mouse model of altered COMT activity. The human Met allele was introduced into the native mouse COMT gene to produce COMT-Met mice, which were compared to their wild-type littermates. The model proved highly-specific: COMT-Met mice had reductions in COMT abundance and activity, compared with wild-types, explicitly in the absence of off-target changes in the expression of other genes. Despite robust alterations in dopamine metabolism, we found only subtle changes on certain cognitive tasks under baseline conditions (e.g. increased spatial novelty preference in COMT-Met mice vs. wild-types). However, genotype differences emerged after administration of the COMT inhibitor tolcapone: performance of wild-type, but not COMT-Met mice, was improved on the 5-choice serial reaction time task after tolcapone administration. There were no changes in anxiety-related behaviours in the tests that we used. Our findings are convergent with human studies of the Val158Met polymorphism, and suggest that COMT’s effects are most prominent when the dopamine system is challenged. Finally, they demonstrate the importance of considering COMT genotype when examining the therapeutic potential of COMT inhibitors.